FLEBAT AVUS FLEBATQUE SOROR - Ruiz de Elvira Prieto, Antonio (Myrtia, 1999)
The author discusses Meziriac’s enmendation Phoebeque soror (Ov. Her. VIII 77) and defends instead of that correction the text of the manuscrips flebatque soror. At the same time suggests, according to the mythographic tradition, that Ovidius in that passage refers to Clitemnestra, Helen’s sister.